Assessment of the Precision ID Identity Panel kit on challenging forensic samples. (November 2020) - Turchi, Chiara; Previderè, Carlo; Bini, Carla; Carnevali, Eugenia; Grignani, Pierangela; Manfredi, Alessandro; Melchionda, Filomena; Onofri, Valerio; Pelotti, Susi; Robino, Carlo; Sorçaburu-Ciglieri, Solange; Tagliabracci, Adriano; et al.
Highlights: The precision of the ID Identity Panel kit was assessed on a large set of challenging forensic samples. A threshold of 50 reads for locus call reduces the frequency of sequencing errors. Replicate analyses assure a low/null rate of typing errors. The high number of markers assures a random match of probability ≤ 1.6 × 10 −13 even for the most challenging samples. PCR-MPS of SNP markers is the ideal approach to the analysis of LCN and degraded DNAs. Abstract: The performance of the Precision ID Identity Panel (Thermo Fisher Scientific) was assessed on a set of 87 forensic samples with different levels of degradation for which a reference sample from the "same donor" or from a "first degree relative" was available. PCR-MPS analysis was performed with DNA input ranging from 1 ng to 12 pg and through 21–26 PCR cycles, in replicate tests, and a total number of 255 libraries were sequenced on the Ion Personal Genome Machine™ (PGM™) System. The evaluation of the molecular data allowed to set a fix threshold for locus call at 50 x which suitably worked even when low amounts of degraded DNA (12 pg) were investigated. In these analytical conditions, in fact, 25 PCR cycles allowed the genotyping of about 50 % and 35 % of the autosomal and the Y-specific markers on average, respectively, for each single amplification with a negligible frequency of drop ins (0.01 %). On the other hand, drop out artefacts reached 18–23 % when low copy number and degraded DNA samples were studied, with surviving alleles showing more than 600 reads in 2.9 % of the cases. Our data pointed out that the Precision ID Identity Panel allowed accurate typing of almost any amount of good quality/moderately degraded DNA samples, in duplicate tests. The analysis of low copy number DNAs evidenced that the same allele of a heterozygous genotype could be lost twice, thus suggesting that a third amplification could be useful for a correct genotype assignment in these peculiar cases. Using the consensus approach, a limited number of genotyping errors were computed and about 37 % of the autosomal markers was finally typed with a corresponding combined random match probability of at least 1.6 × 10 −13, which can be considered an excellent result for this kind of challenging samples. In the end, the results presented in this study emphasize the crucial role of the expert opinion in the correct evaluation of artefacts arising from PCR-MPS technology that could potentially lead to genetic mistyping.